Time course of change in oxygen saturation and peak expiratory flow in children admitted to hospital with acute asthma. Issue 6 (June 1990) - Mihatsch, W; Geelhoed, G C; Landau, L I; LeSouëf, P N
Abstract : The time course for recovery of the arterial oxygen saturation (SaO2) in acute childhood asthma is unknown. Serial measurements of SaO2 were made in 47 children during an acute attack of asthma that required admission to hospital. Adequate serial peak expiratory flow (PEF) measurements were possible in 28 children (mean age 8.3 years; group A), but not in the other 19 children (mean age 3.2 years; group B). Measurements of PEF and SaO2 were recorded twice daily before and 30 minutes after they had received salbutamol by nebuliser. Initial SaO2 values (mean (SD) %) were similar in groups A and B at 92.2 (3.5) and 92.4 (2.9). For the children in group A, PEF plateaued 36 hours after admission and SaO2 plateaued 12 hours later. Mean PEF improved after each dose of nebulised salbutamol during the first 36 hours, whereas mean SaO2 increased only after the first dose. SaO2 increased more rapidly in group B. Length of hospital stay was not related to initial SaO2 or PEF values. These data suggest that in children admitted to hospital for acute asthma arterial oxygen saturation is low at admission, recovers more slowly than airway function, reflects bronchodilatation with salbutamol only when SaO2 is low, and recovers more rapidly in younger children than in older children.